Thin Metal Films: A Method to Form Smooth Films of Liquid Metal Supported by Elastomeric Substrate (Adv. Sci. 10/2018). Issue 10 (17th October 2018) - Hirsch, Arthur; Lacour, Stéphanie P.
Abstract : In article number1800256, Arthur Hirsch and Stéphanie P. Lacour engineer the surface chemistry and topography of silicone rubber (PDMS) with micro‐structured pillars and a gold pre‐coating layer to produce gallium super‐lyophilic substrates. Physical vapor deposition of gallium leads to the formation of smooth and homogeneous films by imbibition of the surface topography rather than coalescence and formation of gallium drops. By capillarity, gallium accumulates in between the pillars up to their top surface, forming a smooth film.